CLIL METHOD IN INFORMATION EDUCATION - WOSSALA, Jan (Trends in education, 2014)
Contribution deals with the method of integrating content and language learning, its advantages and disadvantages. It presents the survey results of the current state using CLIL method in elementary schools and lower grades of secondary schools in the South Moravian Region and Olomouc Region. It presents opportunity to use the CLIL method in information education at schools.
Keywords: CLIL method; education; informatik education.